Enteric Fever: Beyond the Gut - A Multisystem Perspective - Santosh Kumar Singh; Rahil Arora; Rohit Vashisht; Yashas Saipangallu (NMO Journal)
Enteric fever is a systemic disease characterised by the dissemination of Salmonella typhi or Salmonella para typhi. The annual incidence is highest >100 cases/100,000 in India/South Central and Southeast Asia. Central nervous system involvement with Salmonella typhi infection occurs in 2%–40% of patients. hese patients often present with fever, headache, vomiting, seizures, altered states of consciousness, papilloedema and focal neurological deficits within the first few days of fever. In this article, a case of enteric fever with neurological sequelae is presented.